A Comparative Study To Predict Difficult Intubation By Using Palm Print, Prayer’s Sign, And Upper Lip Bite Test In Diabetic And Non- Diabetic Patients - S, Nirmala; B, Kalaivani (Journal of Neonatal Surgery, 2025)
Introduction: Difficult intubation is a most common complication related to anaesthesia when the airway assessment (Mallampati score, thyromental distance) is inadequate or low specificity and sensitivity in some specific conditions. Whereas, diabetic mellitus is a metabolic disease which causes more than 50% of difficult intubation than normal population. This is due to diabetic cheiroarthropathy or diabetic stiff joint syndrome or limited joint mobility syndrome which is characterized by short stature, tight waxy skin, joint rigidity. It occurs when the NON-ENZYMATIC GLYCOSYLATION OF COLLAGENS deposited in joints (first seen in 4th and 5th proximal phalangeal joints and later in Atlanto-occipital joint) in long standing diabetic mellitus. Due to involvement of Atlanto-occipital joint, LIMITED EXTENSION OF HEAD & NECK during intubation leads to difficulties in managing the airway patency. Here, we undertaken the comparative study to predict difficult intubation by using palm print, prayer’s sign, upper lip bite test in diabetic and non-diabetic patients. Methods and Materials: After obtaining Institute Ethics Committee approval, A study design was cross sectional analytical study with a total of 200 patients including diabetics (100) and non-diabetics (100) were assessed pre-operatively for airway indices using palm print, prayer’s sign & upper lip bite test grades were noted. Statistical analysis performed using chi-square test. A p value of < 0.05 is considered as significant. Results: In diabetic mellitus patients, upper lip bite test and palm print was the best predictor for difficult intubation. And in non-diabetic mellitus patients, palm print was the best predictor for difficult intubation. Conclusion: In diabetic and non-diabetic patients, palm print was the best predictor for difficult intubation. Further this study conducted to obtain more accurate results by correlating the palm print with Cormack Lehane grades. Studies with a large sample size are suggested to obtain more accurate results.